Bond and Stock Market Response to Unexpected Earnings Announcements - Datta, Sudip; Dhillon, Upinder S. (Journal of Financial and Quantitative Analysis, 1993)
This study examines whether earnings changes convey information in bond markets and finds a significant positive (negative) reaction to unexpected earnings increases (decreases). The results are consistent whether earnings announcements precede or follow dividend announcements. Thus, earnings surprises convey information to bond markets and changes in firm value are split among bondholders and stockholders. This is in contrast to evidence from studies examining unexpected dividend announcements where bond price reaction is asymmetric. Cross-sectional analysis reveals that bond excess returns are positively related to earnings surprises.